MAPK-Activated Protein Kinases (MKs): Novel Insights and Challenges - Gaestel, Matthias (Frontiers in Cell and Developmental Biology, 2016)
Downstream of MAPKs, such as classical/atypical ERKs and p38 MAPKs, but not of JNKs, signaling is often mediated by protein kinases which are phosphorylated and activated by MAPKs and, therefore, designated MAPK-activated protein kinases (MAPKAPKs). Recently, novel insights into the specificity of the assembly of MAPK/MAPKAPK hetero-dimeric protein kinase signaling complexes have been gained. In addition, new functional aspects of MKs have been described and established functions have been challenged. This short review will summarize recent developments including the linear motif in MKs, the ERK-independent activation of RSK, the RSK-independent effects of some RSK-inhibitors and the challenged role of MK5/PRAK in tumor suppression.